Rancang Bangun Protokol Komunikasi Data Pada Wireless Sensor Network Dengan Topologi Tree Untuk Memantau Gas karbon Monoksida - Shodiq, Achmad Fajar; Susanto, Pauladie; Mardiana, I Dewa Gede Rai (Journal of Control and Network Systems, 2014)
Air pollution is the damage of  air quality which contaminated by pollutants can be changing the composition of air who can be dangerous to humans, animals, and plants. The rapid development of construction, especially industry and technology, and increasing number of vehicles causes air to around us be contaminated by wasting gases combustion  proceeds. Carbon monixide is the most pollutant which is producted in big cities, it is caused by much of out cast gas which is producted by vehicles and proses of industry. Wireless Sensor Network (WSN) can be used to monitor air pollution so can be used an early warning of air pollution at a certain point. With the knowing information is expected to reduce the level of air pollution, especially carbon monoxide gas.From the number of main problems in a implementation of the WSN communication process was one of the problems often experienced. WSN communication  often only rely the protokol communication of WSN devices which are used. If there is one node which experiencing system failures that are below a node cant be perform the communication process, so the sensor data from the node cant be transmit to the center. To solve the problem is proposed a design research on a data communication protocol in WSN, which purpose when there is system failure on one node, there is a backup data lines of communication so that nodes which are below can be transmit sensor data to the central node. In this research design of data communication protocol attempted to tree topology so that higher level of nodes can be set the other nodes of lower level.Communication prosses has been run according with the given data communication protocol. There is a backup lines of comunication if the one nodes failure system experience. Nodes be able to send data result sensor reading of carbon monoxide and also battery condition toward node coordinator with coverage distance in each maximum node is 50m, if used tree topology coverage distance to the all system is 100m. The circuit monitoring of battery condition be able provide information about battery condition with error average 0.03.